Perception Of Factors Affecting The Growth Opportunities Of Women As Managers And Attitude Towards Them - Lim, Kim Suan (1995)
This study was conducted to examine the factors that contribute to the growth ofwomen as managers. These factors include the attitudes of fellow employees towards women as managers and sex-role stereotypes. This study also examined the effect of several biographic and organizational variables including sector affiliation and the nature of responsibilities in the organizations. Data was collected through a structured questionnaire on 133 employees working in 12 organizations in Penang. The results indicated that neither the biographic factors nor organizational factors affect the attitudes towards women as managers. The results are explained in the light of a significant change in the concept of women's role with the increasing number of women entering the workforce.